AIR POLLUTION MODELLING IN MALAYSIA USING GIS AND MACHINE LEARNING ALGORITHMS - TELLA, ABDULWAHEED ADELEKAN (2021)
Spatial modelling and analysis can assist in improving the decision-making process of mitigating bad air quality. One of Malaysia's most harmful air pollutants is particulate matter (PM), which has been used to denote the Air Pollutant Index for over 20 years.